FRI0397 Relationship between Igg Anti-Nr2 Glutamate Receptor Antibodies and Depressive/Anxiety Symptoms in Patients with Systemic Lupus Erythematosus. (10th June 2014) - Mok, C.C.; Chan, K.L.; Diamond, B.
Abstract : Objectives: To study the relationship between anti-NR2 glutamate receptor antibodies (anti-NR2) and depressive/anxiety symptoms in patients with systemic lupus erythematosus (SLE). Methods: Consecutive Chinese patients who fulfilled ≥4 ACR criteria for SLE were recruited. Depressive/anxiety symptoms were assessed by the validated Chinese version of the Hospital Anxiety and Depression scale (HADS) (0-21 points). Serum samples were taken at 10am in the morning for the assay of anti-NR2 antibodies (in-house ELISA using peptide adsorbed to plate and serum diluted 1:100, developed with an anti-human IgG antibody). Disease activity of patients recruited was assessed by SLEDAI and physicians' global assessment (PGA), whereas organ damage since SLE diagnosis was assessed by the ACR/SLICC damage index (SDI). Correlation among anti-NR2 titer, age, sex, HADS-depression score, HADS-anxiety score, SLEDAI, PGA and SDI in various systems was studied by linear regression models. Results: 285 SLE patients were studied (95% women; age 38.9±12.6 years; SLE duration 9.0±7.0 years). At the time of study, 57 (20%) patients had clinically active SLE (SLEDAI ≥5); and 106 (37%) patients had organ damage (SDI score ≥1). The mean SLEDAI was 3.9±4.6 and the mean PGA was 0.36±0.66. Forty-four (15%) patients had HADS-anxiety score of >10 and 28 (9.8%) of patients had HADS-depression score of >10. Anti-NR2 antibodies were present in 154 (54%) patients, defined as titers of greater than the mean+2SD (standard deviation) of healthy controls. Strongly positive values of anti-NR2 (defined as mean+4SD of controls) were found in 90 (32%) patients. Linear regression revealed that anti-NR2 reactivity correlated with SLEDAI score (Beta 0.25; p<0.001), PGA score (Beta 0.31; p<0.001), mean SLEDAI in the preceding 12 months (Beta 0.18; p=0.003), C3 level (Beta -0.25; p<0.001), HADS-depression score (Beta 0.14; p=0.022) and HADS-anxiety score (Beta 0.14; p=0.023), adjusted for age and sex. There was no relationship between anti-NR2 titers and anti-dsDNA titer, total SDI damage score (Beta 0.09; p=0.14), neuropsychiatric damage (Beta 0.06; p=0.32) or SDI scores in other systems. Conclusions: Anti-NR2 antibodies are prevalent in patients with SLE. Anti-NR2 reactivity correlated with disease activity and depressive/anxiety symptoms in SLE patients. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.2633